Analysis of Leading Sectors and Their Influence on Labor Absorption in East Java - Puspitasari, Devi; Setiawati, Ririt Iriani Sri (Universitas KH. Abdul Chalim Mojokerto, 2026)
Economic development is a process designed to enchance conditions with the objective of increasing income, generating employment opportunities, and improving community welfare. As the second-largest economic center in Indonesia, East Java Province has a substantial population; however, its workforce has not been optimally utilized. This study aims to analyze the leading sectors and their influence on labor absorption, with the intention of leveraging this information to create job opportunities. The methodologies employed in this study include LQ analysis, DLQ, and Shift Share analysis to identify leading sectors. Additionally, Class Typology is utilized to determine the economic classification, while panel data linear regression analysis is applied to assess the impact of leading sectors on labor absorption. The findings of the study indicate that each region possesses distinct economic potential. The results of the panel regression analysis reveal that the leading sector has a significant influence on labor absorption.